High-resolution satellite-gauge merged precipitation climatologies of the tropical andes - Manz B. (2016)
This research was funded by the European Institute of Technology (EIT)Climate Knowledge and Innovation Community (Climate-KIC). Buytaert received support from the Ecuadorian PROMETEO program during part of this research. Buytaert and Zulkafli received support from UK NERC grant NE-K010239-1. Willems and Robles received support from Proyecto Cátedra CONCYTEC: “Teledetección en la Desertificación y Sequía.” Gauge data were obtained from HYBAM (http://www.ore-hybam.org) and NOAA NCDC (http://www.ncdc.noaa.gov/cdo-web) as well as from the national weather services of Bolivia (SENAMHI), Colombia (IDEAM), Ecuador (INAMHI), and Peru (SENAMHI), which are not freely accessible in the public domain but can be requested from the institutions. TRMM 2A25 data were obtained from NASA via the Precipitation Processing System (http://pps.gsfc.nasa.gov). The authors would like to thank Bodo Bookhagen and one anonymous reviewer for their valuable comments. The climatological precipitation data sets presented in this study are available at doi.org/10.5285/74a588cc-723c-4a35-ac0c-223f5b92ee36.